Programa Sensijuegos Virtuales con padres de familia para desarrollar la autorregulación emocional en niños de 3 años, Trujillo, 2020 - Lujan Davila, Carolin Cristina (2022)
The piece of research Virtual Sensegames Program which involves parents to develop the 3- year-old children’s emotional self-regulation was made in Trujillo, 2020 and it is aimed to propose a helpful tool to face the worldwide pandemic problem due to Covid 19. This situation has brought about a lot of social changes, even children who are the most vulnerable ones have been affected by changes in their daily routine, activities and schedules. Because of all above stated, this is a descriptive propositive research developed with a sample group to which a pre test was applied to observe their emotional self-regulation. It was composed of 9 three -year-old children in room F, 3 girls and 6 boys from 1368 “Pasitos de Jesús” school. From the pre test results, it was found that 77.78% of children stay in an intermediate level while 22.22% are in a low emotional self-regulation level, so that there is a significative difference in every dimension (reliability, integrity, adaptability and self-control).